Developing Interactive Multimedia for Natural Science in High School - M. Yakub Iskandar; Hendra Hendra; Syafril Syafril; Andri Eka Putra; Dodi Widia Nanda; Rihan Efendi (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2023)
This study aims to create interactive multimedia products in learning Natural Sciences, as well as to analyze how the effectiveness of the products produced. This research uses the method Research and Development (R&D) model Borg & Gall. The research was carried out through five steps, namely planning, initial product development, product validation, product testing, and final product results. Product validity test results were assessed by three validators, one material expert and two media experts. Sources of data were taken using a questionnaire to twenty junior high school students to test the effectiveness of the product being developed. The research results show that; related to the product validity test, material experts gave an average value of 4.7 with a valid category, then related to media experts gave an average value of 4.78 with a valid category. While the results of the analysis of product effectiveness trials in learning obtained an average value of 4.66 meaning that the products that have been produced are in the